Prognostic value of follicular fluid 25-OH vitamin D and glucose levels in the IVF outcome - Liakos Nikolaos; Chalvatzas Nektarios; Messini Christina I; Dafopoulos Konstantinos; Anifandis Georgios M; Pournaras Spyros; Messinis Ioannis E (BMC, 2010)
Abstract Objectives The aim of the present study was to measure serum and follicular fluid 25-OH vitamin D and glucose levels in women who underwent IVF-ET treatment and to further investigate whether the circulating 25-OH vitamin D and glucose levels correlate with IVF success. Methods This prospective observational study included 101 consecutive women who underwent 101 IVF-ICSI ovarian stimulation cycles and were allocated to one of the three groups according to their follicular fluid 25-OH vitamin D concentrations. Group A (n = 31) with less than 20 ng/ml, group B (n = 49) with vitamin levels between 20.1 and 30 ng/ml and group C (n = 21) with more than 30 ng/ml vitamin concentration. Results Follicular fluid vitamin levels significantly correlated with the quality of embryos in total (r = -0.27, p = 0.027), while the quality of embryos of group C were of lower quality as compared to those of groups A and B (p = 0.009). Follicular fluid glucose levels were lower in women of group C as compared to the respective levels of groups A and B (p = 0.003). Clinical pregnancy rate demonstrated in 14.5% in women of group C and 32.3% and 32.7% in groups A and B, respectively (p = 0.047). Conclusion The data suggests that excess serum and follicular fluid vitamin levels in combination with decreased follicular fluid glucose levels have a detrimental impact on the IVF outcome.